Fair Value Accounting and Earnings Management Using LLP and Realized Gains and Losses: Study in Banking Industry Listed on Indonesia Stock Exchange - Ulfa, Ice Maria; Subroto, Bambang; Baridwan, Zaki (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2018)
Abstract: Fair Value Accounting and Earnings Management Using LLP and Realized Gains and Losses: Study in Banking Industry Listed on Indonesia Stock Exchange. This study examines whether earnings management can be limited by the implementation of fair value accounting in banking industry. The main contribution of this study is providing provide empirical evidence about the impact of fair value accounting on earnings management in Indonesia. Earnings management is proxied by loan loss provision (LLP), the realized of gains and losses, and the trade-off between realized gains and losses and LLP following Bratten et al (2013). The study provides empirical evidence that earnings management is still performed by banks, by using LLP, realized gains and losses and also occurs trade-off between LLP and realized gains and losses as means to perform earnings management in accordance with the needs of management. If banks are exposed to fair value accounting, managers will have more flexibility in reporting banks’ financial performance to present a desired earning, by providing them with additional earning managements tools. These findings can be informative for policymakers, banking practitioners, and academics. Keywords: earnings management, fair value accounting, LLP, realized gains and losses, trade-off LLP and realized gains and losses.Abstrak: Akuntansi Nilai Wajar dan Manajemen Laba menggunakan CKPN dan Realized Gains and Losses: Studi pada Industri Perbankan yang terdaftar di Bursa Efek Indonesia. Studi ini bertujuan untuk meneliti apakah manajemen laba dapat dibatasi oleh penerapan akuntansi nilai wajar dalam industri perbankan. Kontribusi dari penelitian ini adalah untuk memberikan bukti empiris tentang dampak penerapan akuntansi nilai wajar pada manajemen laba di Indonesia. Manajemen laba diproksikan oleh cadangan kerugian penurunan nilai (CKPN), realized of gains and losses, dan trade-off antara realized of gains and losses dan CKPN mengikuti model penelitian Bratten et al (2013). Studi ini memberikan bukti empiris bahwa manajemen laba masih dilakukan oleh bank menggunakan CKPN, realized of gains and losses dan juga terjadi trade-off antara CKPN dan realized of gains and losses sebagai sarana manajemen laba sesuai dengan kebutuhan manajemen. Konsekuensi dari paparan bank terhadap akuntansi nilai wajar dapat meningkatkan fleksibilitas manajer dalam melaporkan penghasilan yang diinginkan dengan memberikan mereka alat manajemen laba. Temuan-temuan tersebut dapat bersifat informatif bagi pembuat kebijakan, anggota industri perbankan, dan akademisi. Kata kunci: manajemen laba, akuntansi nilai wajar, CKPN, realized gains and losses, trade-off CKPN dan realized gains and losses.